1998
DOI: 10.1016/s0014-5793(98)00467-0
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 receptor accessory protein interacts with the type II interleukin‐1 receptor

Abstract: IPS I]-hrIL-1L L to mIL-1RII-mIL-1RAcP complex can be inhibited either with antibodies to mIL-1RII (mAb 4E2), or by antibodies to mIL-1RAcP (mAb 4C5). The number of high affinity binding sites in cells stably transfected with the cDNA for mIL-1RII is dependent on the dose of cDNA for mIL-1RAcP used to transfect the cells. The high affinity complex between mIL-1RII and mIL-1RAcP is not preformed by interaction between the intracellular domains of these two transmembrane proteins, rather it appears to require th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 18 publications
(23 reference statements)
1
44
0
1
Order By: Relevance
“…In addition the IL-1RAcP, which is also expressed on microglial cells (Fig. 2), may increase the affinity of IL-1 for IL-1RII as it has been reported that IL-1RAcP associates with IL-1RII (Malinowsky et al 1998). IL-1RII can be shed from the membrane (Sims et al 1993) and, as a soluble form of IL-1RAcP has been described recently (Jensen et al 2000), these two proteins could act as a soluble complex, thus inhibiting actions of released IL-1.…”
Section: Discussionmentioning
confidence: 83%
“…In addition the IL-1RAcP, which is also expressed on microglial cells (Fig. 2), may increase the affinity of IL-1 for IL-1RII as it has been reported that IL-1RAcP associates with IL-1RII (Malinowsky et al 1998). IL-1RII can be shed from the membrane (Sims et al 1993) and, as a soluble form of IL-1RAcP has been described recently (Jensen et al 2000), these two proteins could act as a soluble complex, thus inhibiting actions of released IL-1.…”
Section: Discussionmentioning
confidence: 83%
“…As shown in Figure 2D, overexpression of sIL-1RAcP likely formed complexes on the cell surface of IL-1␤ bound to type II receptors. This complex as the type II receptor decoy mechanism was first proposed by Malinowsky et al (25) and Lang et al (26), and accounts for the ability of sIL-1RAcP to reduce B lymphocyte activation. It is thus likely that low levels of type II receptors on T lymphocytes prevent suppression of T lymphocytes in vivo and in vitro by sIL-1RAcP.…”
Section: Cell Selectivity Of Decoy Il-1rmentioning
confidence: 89%
“…This receptor, which lacks a cytoplasmic domain and cannot participate in signal transduction, functions as a decoy receptor by competitive binding to IL-1␤ (24) ( Figure 2B). The type II receptor can also form an inactive complex with the IL-1RAcP ( Figure 2B), preventing the cell from participating in signal transduction (25,26).…”
Section: What Accounts For the Differences Between Overexpression Of mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the IL-1RII can also indirectly determine the availability of the IL-1RAcP. The amount of IL-1RII expression on the membrane determines the sensitivity of the cell toward IL-1, and membrane IL-1RAcP is able to interact with the IL-1RII (18,47). Therefore, abundant expression of the IL-1RII will not only lead to scavenging of IL-1, but will also reduce the available IL-1RAcP to form a signaling complex with the type I receptor, shifting the balance in favor of the sIL-1RAcP for receptor competition with the IL-1RAcP for formation of receptor complexes with IL-1RI.…”
Section: Discussionmentioning
confidence: 99%